2019
DOI: 10.3390/molecules24101876
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities and Chemical Constituents of Essential Oils from Piper cubeba Bojer and Piper nigrum L.

Abstract: In this study, we evaluated antioxidant, antihyperuricemic, and herbicidal activities of essential oils (EOs) from Piper cubeba Bojer and Piper nigrum L.; two pepper species widely distributed in tropics, and examined their chemical compositions. Dried berries of P. cubeba and P. nigrum were hydro-distilled to yield essential oil (EO) of 1.23 and 1.11% dry weight, respectively. In the antioxidant assay, the radical scavenging capacities of P. cubeba EO against DPPH and ABTS free radicals were 28.69 and 24.13% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Similar to the aforementioned compounds, the sesquiterpenes were also detected in high initial relative amounts with 14.32 μg/100 g, 11.47 μg/100 g, 10.85 μg/100 g, 8.40 μg/100 g, and 6.09 μg/100 g, respectively, and tend to decrease or disappear under the roasting condition over time. Each compound elicits distinct odors and is derived from various plants, medicinal herbs, and their essential oils; spice, fresh, and ginger‐like odors from ginger essential oils for zingiberene (Ibanez & Blaszquez, 2019); wood odors from oregano for β‐sesquiphellandrene (Cheng et al., 2007); balsamic odors from lemon, oregano, and cubeb essential oils for β‐bisabolene (Cheng et al., 2007); wood and spice odors from clove, rosemary, and hop essential oils for caryophyllene (Fu et al., 2007); and wood and spice odors from angelica oils, basil oils, bay leaf oils, cananga leaf oils, and cajeput oils for α‐copaene (Andriana, Xuan, Quy, Tran, & Le, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the aforementioned compounds, the sesquiterpenes were also detected in high initial relative amounts with 14.32 μg/100 g, 11.47 μg/100 g, 10.85 μg/100 g, 8.40 μg/100 g, and 6.09 μg/100 g, respectively, and tend to decrease or disappear under the roasting condition over time. Each compound elicits distinct odors and is derived from various plants, medicinal herbs, and their essential oils; spice, fresh, and ginger‐like odors from ginger essential oils for zingiberene (Ibanez & Blaszquez, 2019); wood odors from oregano for β‐sesquiphellandrene (Cheng et al., 2007); balsamic odors from lemon, oregano, and cubeb essential oils for β‐bisabolene (Cheng et al., 2007); wood and spice odors from clove, rosemary, and hop essential oils for caryophyllene (Fu et al., 2007); and wood and spice odors from angelica oils, basil oils, bay leaf oils, cananga leaf oils, and cajeput oils for α‐copaene (Andriana, Xuan, Quy, Tran, & Le, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Lawrence [ 37 ] reported that the main components were α-copaene, β-cubebene, allo-aromadendrene, γ-muurolene, and germacrene D, followed by δ-cadinene and β-caryophyllene. In the recent study of Andriana et al [ 38 ], the authors found that terpinen-4-ol (42.41%), α-copaene (20.04%), and γ-elemene (17.68%) were the major components. Based on the above literature descriptions, our chemical composition results are still different, and confirm the originality of our P. cubeba fruit’s essential oil.…”
Section: Discussionmentioning
confidence: 99%
“…General information : P. nigrum (black pepper, Piperaceae) is one of the world’s most widely used spices and it is distributed throughout the tropics and subtropics, as in Southwestern India. In Brazil, this plant has confirmed occurrences in different phytogeographic domains, such as the Amazon, Atlantic Forest, and Pantanal [ 156 , 157 ].…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%
“…Its fruits are usually dried and used as spices and seasonings [ 158 , 159 ]. Black pepper is also used to produce pepper oil and oleoresin, for the production of foods and also for perfumery [ 156 , 157 , 160 ]. Vitamins A, C, E, K, choline, folic acid, pyridoxine, riboflavin, thiamin, and niacin can be found in the black pepper constitution.…”
Section: Bioactive Compounds From Eos Of Spice Plantsmentioning
confidence: 99%
See 1 more Smart Citation